EFL Students’ Beliefs on Self-Assessment on Speaking Performance: Case on Indonesian Pre-Service Teachers - Hermagustiana , Istanti; Ahada, Ichi (Borneo Educational Journal (Borju), 2025)
This research aims to explore student beliefs regarding self-reported feedback on their speaking performances in English classes. It investigates what beliefs students hold about receiving self-assessed evaluations and delves into how these assessments can identify both strengths and weaknesses in English-speaking abilities. Using a qualitative case study approach involving interviews with three highly self-regulated learners, the study highlights the significance of self-assessment for improving speaking skills. While acknowledging that self-assessment has its limitations—such as insufficient English proficiency, restricted practice opportunities, and emotional hurdles—the research emphasizes incorporating external feedback from peers, teachers, or technological tools to enhance learner comprehension of their speaking capabilities. Ultimately, addressing these challenges through integrated teaching methods could optimize the efficacy of self-assessment practices in enhancing language learning outcomes.